STUDI LITERATUR: EKSISTENSI RADIO PADA ERA KONVERGENSI MEDIA - Prasasti, Tika (Commsphere: Jurnal Ilmu Komunikasi, 2023)
This research examines the existence of radio in the era of media convergence. The research aims to discover how radio exists in the era of media convergence, where new media emerged, making it easier for people to find information. This research uses a qualitative approach to the type of literature study with a historical review—data collection techniques through reviewing books and literature and references related to the research being carried out. The research results show that radio broadcasting can survive in the era of media convergence by making new media an opportunity, not a threat, by utilizing the internet to create websites and social media for archiving content and sharing information about broadcast programs. Keywords: Radio, Technology, Internet, Media Convergence